GAMBARAN PERILAKU PENCEGAHAN HIV DAN AIDS PADA LELAKI SUKA LELAKI (LSL) DI KOTA KUPANG TAHUN 2014 - Kana, Indah M.P; Nayoan, Christina R; Limbu, Ribka (Unnes Journal of Public Health, 2016)
HIV prevalence among men who have sex with men (MSM) in Indonesia increasing time to time, 7% in 2009 to 12,8% in 2013. The high prevalence of HIV in this population is associated with the low level of prevention, because as lack of information and low condom use. The purpose of this study was to obtained in-depth information about the behavior of HIV and AIDS prevention in MSM assessed the intention, social support, access to information, personal autonomy, and action situation. Design of this study is descriptive using qualitative approach. Five informants were selected by purposive sampling from IMOF Kupang Community for indepth interview, using guidance structured interview. The result was transcipted then classified according to the themes that emerged. The results shows that informants were attitude, subjective norm, and behavior control the influencing their intention to HIV and AIDS prevention. MSM obtained social support from the MSM community friends and KPA, the support are emotional support and information. Informants get the information about HIV and AIDS from socialiszations and mass media (internet). The informants also have their own initiatives for preventing HIV and AIDS (using condoms during sex). Health services can be accessed easily by the informant because there is a cooperation with the health institution. From this research it can be concluded that informants have a good intention, social support, the availability of information acces, personal autonomy and action situation to prevent HIV and AIDS.